2019
DOI: 10.1186/s12889-019-7380-2
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and self-rated health: evidence from a national survey of homeless people in Spain

Abstract: Background Internationally, acute homelessness is commonly associated with complex health and social care needs. While homelessness can be understood as an outcome of structural housing exclusion requiring housing led solutions, the health care issues faced by homeless people equally require attention. A substantive evidence base on the health needs of homeless people exists, but relatively little is known about what influences the self-rated health of homeless people. This article presents new ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 68 publications
7
23
0
1
Order By: Relevance
“…A larger self-reliant transitionally homeless group experiences living rough for shorter periods also exist with more favourable health indicators (1). Our data on the presence of chronic diseases support this type of distribution in the roo ess group, in addition with the concordance of a recent Spanish research, in which less than half of the examined population was heavy drinker (39).…”
Section: Discussionsupporting
confidence: 91%
“…A larger self-reliant transitionally homeless group experiences living rough for shorter periods also exist with more favourable health indicators (1). Our data on the presence of chronic diseases support this type of distribution in the roo ess group, in addition with the concordance of a recent Spanish research, in which less than half of the examined population was heavy drinker (39).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, our unhoused study sample also skewed to be mostly white (47.1%) and non-Hispanic (68.6%), but was evenly split between males and females. The existing research on the association between sex and well-being in unhoused individuals suggests that women may be a particularly vulnerable subgroup [ 31 ]. Unhoused women are less satisfied with their health and empowerment, have lower self-esteem, and experience more psychological distress than unhoused men [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, although findings are mixed as to the degree of vulnerability, the risks of homelessness associated with health and well-being may be greater for people of color than for white people, especially for women [ 33 ]. Age also plays a role in the experience of homelessness: older age among unhoused individuals has been associated with worse physical health and more limited social support [ 31 , 34 ]. Thus, the demographics of a homeless individual may influence their experience of homelessness and how they report their well-being.…”
Section: Discussionmentioning
confidence: 99%
“…If one considers social impact to infer social improvements attained from the transference of the research results (Pulido et al, 2018), the social impact of psychology has served homeless people mostly by informing intervention programs related to preventing and responding to substance abuse (Davidson et al, 2013), healthcare (Salem and Ma-Pham, 2015;Fajardo-Bullón et al, 2019), sexual risks (Pedersen et al, 2018), or mental illnesses (Noël et al, 2016;Fond et al, 2019) -key problems that also psychology has studied and found to be connected to homelessness. Such strategies have often been centered on tackling the challenges that homeless people face, such as those mentioned above.…”
Section: Introductionmentioning
confidence: 99%